Tajni współpracownicy Milicji Obywatelskiej na Ziemi Lubuskiej (1945-1989) = The unofficial collaborators of the Citizens? Militia in Lubusz Land (1945-1990) - Krystians, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
There is a general conviction that the activity of the unofficial collaborators (Tajni Współpracownicy, TW) was connected only with the communist security apparatus (UB/SB). However, similar methods of work were also used, though not on such a large scale, by the other formations of the repression apparatus, including the Citizens? Militia (Milicja Obywatelska, MO).
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia